Calcareous nannoplankton evolution and the Paleogene greenhouse to icehouse climate-mode transition - Newsam, C (UCL (University College London), 2017)
This thesis addresses calcareous nannoplankton evolutionary and palaeoecological response across the Paleogene greenhouse to icehouse transition using newly drilled material from Sites U1408 and U1411 (IODP Expedition 342) in the North Atlantic. Calcareous nannoplankton were the dominant oceanic phytoplankton group in the early Paleogene yet declined in diversity and underwent significant assemblage restructuring through the middle Eocene to early Oligocene, coinciding with major climatic reorganisation. However the structure and timing of this nannoplankton response is poorly constrained due to few records of appropriate stratigraphic resolution. Here, exceptionally preserved calcareous nannofossils from stratigraphically expanded packages of Paleogene clay-rich drift sediments from IODP Expedition 342 are used to document diversity loss and population shifts in order to interpret the relationship between plankton evolution and palaeoclimatic and palaeoceanographic change in the North Atlantic across this key interval, with focus on abrupt climatic change at the Middle Eocene Climatic Optimum (MECO) and the Eocene-Oligocene transition (EOT). Results indicate low speciation rates combined with relatively high extinction rates drove calcareous nannoplankton diversity loss through this interval and palaeoecological analysis highlights three key intervals; middle Eocene stability, incorporating muted assemblage response to transient warming at the MECO, the late Eocene transitional phase and the EOT and early Oligocene population restructuring, with major assemblage shifts controlled by intensified surface water cooling and increased nutrient availability. Palaeoclimatic and palaeoceanographic changes through this transition led to reduced optimal habitat space for this phytoplankton group resulting in decline and extinction in many taxa and the proliferation of select opportunists at the onset of the icehouse world.